Constituents from stem barks of Anacolosa poilanei Gagnep. (Olacaceae) - Thuy Ai, Doan Thi; Thanh Van, Trinh Thi; Mai Huong, Doan Thi; Litaudon, Marc; Tram, Le Huyen; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Four compounds were isolated from the stem barks of Anacolosa poilanei Gagnep. Theirs structures were established by spectroscopic analysis including MS and NMR. Accordingly, the isolates were identified as trichadenic acid B (1), trichadonic acid (2), amentoflavone (3) and β-sitosterol (4).